Forensic investigation of stolen-recovered and other crime-related vehicles - Stauffer, Eric, 1975-; Bonfanti, Monica S. (Elsevier/Academic Press, 2006)
Forensic Investigation of Stolen-Recovered and Other Crime-Related Vehicles is the ultimate reference guide for any auto theft investigator, crime scene technician, criminalist, police investigator, criminologist, or insurance adjuster. In addition to a thorough treatment of auto theft, the book covers vehicles involved in other forms of crimedealing extensively with the various procedures and dynamics of evidence as it might be left in any crime scene. An impressive collection of expert contributors covers a wide variety of subjects, including chapters on vehicle identification, examination of burned vehicles, vehicles recovered from under water, vehicles involved in terrorism, vehicle tracking, alarms, anti-theft systems, steering columns, and ignition locks. The book also covers such topics as victim and witness interviews, public and private auto theft investigations, detection of trace evidence and chemical traces, vehicle search techniques, analysis of automotive fluids, vehicle registration document examination, and vehicle crime mapping. * Extensively researched and exceptionally well-written by internationally-recognized experts in auto theft investigation and forensic science * All the principles explained in the text are well-illustrated and demonstrated with more than 450 black and white and about 100 full-color illustrations, many directly from real cases * Serves as both a valuable reference guide to the professional and an effective teaching tool for the forensic science student.